C-Reactive Protein Levels in relation to Incidence of Hypertension in Chinese Adults: Longitudinal Analyses from the China Health and Nutrition Survey - Bo Chen; Yuze Cui; Mengyun Lei; Wenlei Xu; Qiongjie Yan; Xiaotong Zhang; Minghui Qin; Shaoyong Xu (International Journal of Hypertension)
Objective. To explore the association between high sensitivity C-reactive protein (hs-CRP) levels and incident hypertension, as well as the association between hs-CRP levels and related covariates, in a Chinese adult population. Methods. This study was based on the China Health and Nutrition Survey, a continuing open, large-scale prospective cohort study. Adult participants who were free of hypertension were included at baseline survey in 2009 and were followed up in 2015 (follow-up rate: 77.45%). The hs-CRP was measured using the immunoturbidimetric method and divided into three groups: low-risk group (0 ≤ hs-CRP <1 mg/L), average-risk group (1 ≤ hs-CRP <3 mg/L), and high-risk group (3 ≤ hs-CRP ≤10 mg/L). Definite diagnosis of hypertension in the follow-up survey in 2015 was the endpoint event of this study. The areas under the curve (AUC) of the receiver operating characteristic (ROC) curve analyses were used to evaluate the predictive value of the hs-CRP. Results. 3794 participants were finally included as study sample, of whom 912 developed hypertension during a 6-year follow-up period (incidence: 24.1%). The incidences of hypertension in hs-CRP low-risk, average-risk, and high-risk groups were 17.6% (200/1135), 25.9% (521/2015), and 29.7% (191/644), respectively. Spearman’s correlation analyses showed that there was significant positive correlation between hs-CRP levels and waist circumference, total triglycerides, total cholesterol, age, body mass index, and homeostasis model assessment of insulin resistance index. Stepwise regression analyses showed that participants in the hs-CRP high-risk group had a 46.2% higher risk of developing hypertension compared with those in the hs-CRP low-risk group (odds ratio: 1.462, 95% confidence interval: 1.018–2.101). Baseline systolic and diastolic blood pressure levels and waist circumference contributed the most to the development of hypertension with R2 of 0.076, 0.052, and 0.039, respectively, while hs-CRP had lower area under the curve (AUC) for hypertension, adding baseline BP and WC to the prediction model increased the AUC to 0.708 (95% CI: 0.681–0.735). Conclusion. This study revealed a weak positive association between CRP levels and future incidence of hypertension in the Chinese population. The combination of hs-CRP with baseline BP and waist circumference (WC) had a higher predictive value for hypertension (AUC: 0.708), but the predictive value was still limited.